Evaluation of efficiency and environmental safety of leaching metals from ore: ways of development and prospects - Lyashenko, Vasil; Khomenko, Oleh; Chekushina, Tatiana; Dudar, Tamara; Topolnij, Fedor (Technology audit and production reserves, 2021)
The object of research is traditional mining technologies and technical means in combination with underground block leaching (UBL) of metals from rock ores with their preliminary crushing with explosives in installations mounted in mine workings. One of the most problematic areas is the difficulty of achieving a given crushing quality, as well as the required height of ore storage in the chamber for the subsequent leaching of metals and a loosening factor, taking into account the control of the energy of explosive destruction of rock ores. The study used: – data from literary sources and patent documentation in the field of technologies and technical means for UBL of metals from ores in energy disturbed massifs, substantiation of technological parameters of operational blocks; – laboratory and production experiments; – physical modeling of metal extraction from ores from the average linear size of a piece of blasted ore. Analytical studies, comparative analysis of theoretical and practical results using standard and new methods were carried out with the participation of the authors. It was found that the most intensive infiltration leaching occurs when the size class of ore lumps is –100+0 mm. Metals are extracted from fractions –200+100 mm less intensively and for a longer time. To neutralize and flush the spent ore mass, it is recommended to treat it with lime solution and mine water through wells for supplying leaching solutions (irrigation system). The protection of the hydrogeological environment is carried out by silting the bottom of the chamber for collecting productive solutions with clay solution and by constant monitoring of mine water pollution in the zone of UBL influence. On the basis of the positive results obtained from the study and implementation of technologies for UBL of metals from rock ores during the development of block 5–86, in accordance with the recommendations issued, the same approach was used for blocks 5–84–86 and 5–88–90, as well as industrial experimental block 1–75–79. Due to the involvement in the production of substandard ores, the raw material base for the extraction of metals, at the operating mines, can be increased by 1.4–1.6 times. The research results can be used in underground mining of ore deposits of complex structure in Ukraine, the Russian Federation, the Republic of Kazakhstan and other developed mining countries of the world.